(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
During the eighteenth and nineteenth centuries, the Khiva Khanate occupied a strategically important position in Central Asia, functioning as a key intermediary between Eastern production zones and Western consumption markets. While traditionally viewed as a regional power primarily engaged in trade with neighboring khanates and the Russian Empire, recent historical evidence demonstrates that Khiva was indirectly integrated into wider global trade networks extending to Western Europe and British India. This article examines the structure, scale, and direction of Khiva Khanate exports, focusing specifically on their penetration into Western European and British Indian markets. By analyzing commodity composition, trade routes, and intermediary mechanisms, the study aims to reassess Khiva’s role in early modern global commerce and to challenge the notion of Central Asian economic isolation.